Orofacial Cleft Frequency Differences Depending on Geographic Origin: Coast vs. Inland - Vieira, Alexandre Rezende; Furtado, Paulo Germano Cavalcanti; Filho, Valdécio Vasconcelos Lacerda; Pereira, Jéssica Amorim Teotônio; Tenório, Isabelle Silvério; Luna, André Macedo; Filgueiras, Vitor Marques; Lacerda, Rosa Helena Wanderley (Frontiers in Dental Medicine, 2021)
Objective: Cleft lip and or palate is the most common congenital anomaly in the human face with a multifactorial and complex etiology. Although many studies have been developed, the role of the environment is still unclear. This study aims to test the hypothesis that differences in lifestyle and environment change the reproductive risks of orofacial clefts. Methods: 2,422 medical records of individuals born with cleft lip and or palate in a reference center in the Northeast of Brazil over a period of 30 years were analyzed. Data on the cleft type, geographic origin of the patient (coast or inland), presence of associated congenital anomalies or syndromes, maternal age, and maternal parity were recorded. Differences in frequencies between the cleft types were compared based on geographic origin, maternal age, and parity. Chi-square, Student's t, Kruskal-Wallis, and logistic regression were used to analyze the interference of covariables on the cleft type. Results: The distribution of cleft types was significantly different between the coastal and inland areas (chi-square test, p< 0.0001). A higher frequency of cleft lip with or without palate was observed inland (chi-square test, p= 0.0006), while cleft palate only (chi-square test, p= 0.003) and rare facial clefts (chi-square test, p= 0.004) were more frequent in the coastal area. No difference was found in the distribution of maternal age (t test, p>0.05) between the two geographic areas, but parity was higher inland (t test, p=0.04). Logistic regression suggested that parity explained just a small portion of the differences in frequency between cleft types of the coast versus inland. Conclusion: Frequency of orofacial cleft types differs by geographic area in this region of the South American continent.